Correlation of lymphocyte subsets and inflammatory biomarkers with disease severity in COVID-19 patients - Abbas, Khawar; Musharraf, Wajiha; Zafar, Mirza Naqi; Lal, Jawahar; Dodani, Sunil; Rizvi, Syed Adibul Hassan (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the correlation of lymphocyte subsets and soluble serum inflammatory biomarkers with disease severity in coronavirus disease-2019 infection. Method: The retrospective study was conducted at the Department of Immunology, Sindh Institute of Urology and Transplantation (SIUI), Karachi, Pakistan from September 1 to November 30, 2021, and comprised data of patients admitted from June to July 2021 who tested positive for coronavirus disease-2019 on the basis of reverse transcription-polymerase chain reaction of nasopharyngeal swab specimens. The patients were categorised into severe group A and non-severe group B. Initial investigations included complete blood count, neutrophil-to-lymphocytes ratio, C-reactive protein, D-Dimers and serum ferritin levels. Lymphocyte subsets included cluster of differentiation-3+, cluster of differentiation-4+/ cluster of differentiation-3+, cluster of differentiation-8+ T lymphocytes, cluster of differentiation-19+B lymphocytes, cluster of differentiation-16+ cluster of differentiation-56+ Natural Killer cells and serum cytokine levels of interleukin-2, interleukin-4, interleukin-6, interleukin-10, tumour necrosis factor-alpha and interferon gamma. They were correlated with disease severity. Data was analysed using SPSS 20. Results: Of the 54 patients., 33(61.1%) were males and 21(38.9%) were females. There were 29(53.70%) patients in group A with median age 52 years (interquartile range: 43.5-65 years), and 25(46.29%) in group B with median age 50 years (interquartile range: 36.5-59 years) (p=0.241). Disease was significantly more severe in male patients compared to female (p=0.002). In group A, cluster of differentiation-3+ T cells were reduced in 21(72.4%) patients, cluster of differentiation-8+ T cells in 16(55.2%), cluster of differentiation-4+ T cells in 23(79.3%) and cluster of differentiation-19+ B cells in 8(27.6%). In group B, cluster of differentiation-3+ T cells were reduced in 10(40%) subjects, cluster of differentiation-8+ T cells in 7(28%), cluster of differentiation-4+ T cells in 12(48%) and cluster of differentiation-19+ B cells in 4(16%) patients. Serum cytokine levels were not significantly different between the groups (p>0.05). In group A, 7(24.13%) patients died, and in such cases, the neutrophil-to-lymphocytes ratio was significantly higher (p=0.037). Conclusion: Pro-inflammatory markers and cytokine levels increased, while lymphocyte subsets decreased with increasing severity of the disease. Key Words: COVID-19, C-reactive protein, Ferritin, Lymphocyte subsets, Interleukin-6.